Pijat Kaki dengan Losion Magnesium Menurunkan Stres Narapidana Perempuan - Udani, Giri; Manurung, Idawati; Yulyuswarni, Yulyuswarni (Poltekkes Kemenkes Tanjung Karang, 2021)
Prisoners experience stress during detention, and this stress must be removed so that the behavior and mentality of prisoners can be quickly restored. Foot massage is one of the non-pharmacological therapies in stress management, which makes individuals more relaxed and able to avoid excessive stress reactions such as headaches, insomnia, anxiety, physical and mental fatigue. Magnesium is a mineral that plays an important role in the body's metabolism. Magnesium deficiency can cause migraines, insomnia, leg cramps, anxiety, arrhythmias, diabetes mellitus, and hypertension. Foot massage with magnesium lotion is expected to provide a relaxing effect as well as magnesium intake so that it can overcome the stress experienced by prisoners. This study aims to determine the effect of foot massage magnesium lotion on the stress level of female prisoners. The research method is a quantitative quasi-experimental design with a pre-test-post-test approach on 120 female prisoners by comparing stress levels before and after doing foot massage with magnesium lotion for 14 days. Foot massage with magnesium lotion is done independently. Based on the results of the study, there was a significant difference between stress levels before and after the intervention, there was no significant difference between the stress levels of respondents who had long been detained and those who had just been detained. Multivariate analysis showed that the main factor in stress levels was the sentence period. Foot massage using magnesium lotion is a supporter of reducing stress levels. This therapy should still be done because it helps reduce stress and is carried out independently by prisoners.